Implementation of Economic Rights Principles on Trademark In Trading of Product in The Pandemic Covid-19 Era - Delfiyanti Delfiyanti (SASI, 2021)
In accompany with the tight trading competition, it is imply that trademark plays significant role to known as the special product in common and had the power and useful when it managed in appropriate. Trademark is not just the word related to the product or collection only but the process and business strategy. Therefore, trademark have a value and equity. Thus equity becomes important as the value to be a benchmark of product in the marketplace. However, the pandemic of Covid-19 that struck since beginning of 2020 had an enormous impact to the whole states in the world including Indonesia. The pandemic was bring worst influences to the economic and trading. The deadly disease automatically was paralyze an economy and trading. It is caused by restriction of people to drive and influences the product movement. Temporarily, export-import activities delayed as restriction of transportation entry among the states. Finally, Indonesia forced close for in and out flight of territory. The situation influence to the implementation of Economic Right of trademark right attach to the import and export products in Indonesia.